Highly transparent poly(glycidyl methacrylate-co-acryloisobutyl POSS) for 100 μm-thick submicron patterns with an aspect ratio over 100. Issue 58 (5th July 2017) - Kim, Kwanghyun; Yu, Sunyoung; Kim, Sung-Wook; Kim, Taegeon; Kim, Sang-Min; Kang, Se-Young; Han, Seung Min; Jang, Ji-Hyun
Abstract : This is the first report on the fabrication of defect-free submicron structures with more than 100 μm thickness and an aspect ratio over 100. Abstract : This is the first report on the fabrication of defect-free submicron structures with more than 100 μm thickness and an aspect ratio over 100. Highly transparent poly(glycidyl methacrylate- co -acryloisobutyl POSS) (PGP) was synthesized via radical polymerization. The mechanical properties of the PGP submicron structure displayed a Young's modulus of 6.09 GPa and a hardness of 0.16 GPa, 4.2 and 8 times, respectively, than those of SU8 nanopatterns. These enhancements enable the utilization of ultrathick 2D-/3D-submicron structures as an ideal platform for microelectromechanical systems, big data storage systems, energy devices, etc.